Relevance of the Studying Quality of Life Indicator in Children with Allergic Diseases - O.Ya. Tkachenko (Zaslavsky O.Yu., 2013)
This overview focuses on global issues and conceptual approaches to understanding the quality of life. Despite the fairly large number of questionnaires for children, the data in this article demonstrate that the definition of quality of life should be more widely used in pediatric studies. Recently, this criterion is most frequently used to analyze the quality of medical care for patients with chronic diseases. Assessment of quality of life in children with allergic diseases, such as bronchial asthma, allergic rhinitis, urticaria, is especially important. This is primarily due to the high prevalence of allergic pathology, as well as its significant influence on the daily lives of patients, which certainly involves important social and economic spheres of activity. Improving quality of life is strongly correlated with the appropriate treatment, which is clearly demonstrated by the patients with bronchial asthma, especially in the pediatric population.